Inspiring Imagination: Digital Projects As a Post-Reading Activity in Foreign Language Lessons - Yanbastieva-Petrova, Lina (Lyuboslovie, 2024)
This paper explores the role of education in equipping students with the diverse skills needed for success in the 21st century, with a focus on mastering reading skills and digital literacy. It highlights the advantages of sparking students’ imagination and curiosity and the benefits of implementing project-based learning principles in foreign language classrooms, where learners enhance language proficiency while developing critical thinking, creativity, collaboration, and other “21st-century skills”. The paper also examines some key principles of teaching reading, focusing on the use of post-reading activities to inspire imagination and creative expression through working on digital projects. Some practical ideas for utilizing educational platforms in these tasks are discussed, with examples drawn from projects created by students from an innovative class at Yoan Ekzarh Balgarski Secondary School, Shumen. The results indicate that working on post-reading digital projects not only improved students' reading comprehension and language skills but also enhanced their confidence and motivation in using various educational platforms for creating digital content, such as mozaBook and Buncee. Students demonstrated improved teamwork skills and problem-solving abilities when engaged in designing digital projects, which facilitated deeper learning and greater retention of information. The study concludes that integrating digital project-based learning principles into reading instruction can significantly enrich students’ educational experience by supporting skill development relevant to the challenges of the modern world. The findings underscore the importance of incorporating creative and interactive methods in foreign language teaching to better prepare students for future academic and career success.